Fragments of Target Cells are Internalized into Retroviral Envelope Protein-Expressing Cells during Cell-Cell Fusion by Endocytosis - Izumida, Mai; Kamiyama, Haruka; Suematsu, Takashi; Honda, Eri; Koizumi, Yosuke; Yasui, Kiyoshi; Hayashi, Hideki; Ariyoshi, Koya; Kubo, Yoshinao (Frontiers in Microbiology, 2016)
Retroviruses enter into host cells by fusion between viral and host cell membranes. Retroviral envelope glycoprotein (Env) induces the membrane fusion, and also mediates cell-cell fusion. There are two types of cell-cell fusions induced by the Env protein. Fusion-from-within is induced by fusion between viral fusogenic Env protein-expressing cells and susceptible cells, and virions induce fusion-from-without by fusion between adjacent cells. Although entry of ecotropic murine leukemia virus requires host cell endocytosis, the involvement of endocytosis in cell fusion is unclear. By fluorescent microscopic analysis of the fusion-from-within, we found that fragments of target cells are internalized into Env-expressing cells. Treatment of the Env-expressing cells with an endocytosis inhibitor more significantly inhibited the cell fusion than that of the target cells, indicating that endocytosis in Env-expressing cells is required for the cell fusion. The endocytosis inhibitor also attenuated the fusion-from-without. Electron microscopic analysis suggested that the membrane fusion resulting in fusion-from-within initiates in endocytic membrane dents. This study shows that two types of the viral cell fusion both require endocytosis, and provides the cascade of fusion-from-within.